Extent of computerization of state college and university libraries in the Philippines - Salvador, Virginia P. 1964- (Institute of Library Science, University of the Philippines Diliman, 1998)
Information is generated left and right and it is the responsibility of the libraries to provide the right information to the right person at the right time. With information explosion, how can libraries be able to provide access to information more effectively and efficiently? State colleges and universities (SCU) are addressing this problem through the use of computer technology. It is towards this end that this research is carried out. This study is an investigation on which libraries of state colleges and universities in the Philippines are already computerizing their operations.